Komunikasi Tanpa Nama yang Jujur dan Terbuka : Studi Kasus pada Akun @Komunitasmaunangisaja di Twitter (X) - Municha Ariyanti; Ratnaningrum Z.D; Moch. Ichdah Hayau Lailin (Institut Nalanda, 2024)
This study analyzes the phenomenon of anonymous communication on the Twitter account (X) @komunitasmaunangisaja and its impact on users' mental health using a transcendental phenomenology approach. Data collection methods include direct observation, content analysis of tweets, and in-depth interviews with account users. Findings indicate that anonymous communication on this account positively impacts mental health by reducing feelings of isolation and enhancing emotional well-being. Users feel more free to express their feelings without fear of judgment, helping to alleviate emotional burdens and gain community support. However, there are also negative impacts, such as dissatisfaction with received responses and the risk of anonymity abuse for negative behavior. The study also reveals that users frequently turn to anonymous communication to cope with stress, anxiety, and depression. This platform provides a space for sharing deep emotions and experiences, facilitating a sense of togetherness and emotional release. Community support helps users feel validated and understood, contributing to overall mental health improvement. This study highlights the importance of such platforms in creating a safe environment for emotional expression, ultimately contributing to better mental well-being, and emphasizes the need for more supportive online communities